Effect of Problem Solving and Numbered Heads Together Models on Cooperation Character and Critical Thinking of Fourth Graders in Pancasila Profile (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of the combined learning model of Problem Solving with Numbered Head Together (NHT) on the character of mutual cooperation and critical reasoning abilities of fourth-grade students of SD Negeri Kanigoro 03. This type of research uses a quantitative approach with a Posttest Only Non-Equivalent Control Group Design. The research subjects consisted of two classes, namely class IV A as the experimental group and class IV B as the control group, each consisting of 23 students. The research instruments included an observation sheet of mutual cooperation character and a critical reasoning ability test. Data analysis was carried out through normality, homogeneity, and t-test using SPSS with a significance level of 5%. The results showed that the data were normally distributed and homogeneous. The t-test produced a calculated t value of 2.940 > t table 2.015 with a significance of 0.019 for the character of mutual cooperation and a calculated t value of 2.343 > t table 2.015 with a significance of 0.024 for critical reasoning abilities. These results demonstrate that the combined Problem Solving and NHT models significantly enhance students' mutual cooperation and critical reasoning skills. Therefore, implementing this model effectively develops students' cognitive competencies and character, aligned with the Pancasila student profile.